2002
DOI: 10.1016/s0191-8869(01)00100-3
|View full text |Cite
|
Sign up to set email alerts
|

Locus of control and learning to cooperate in a prisoner's dilemma game

Abstract: Boone et al. (Boone, C., De Brabander, B., & van Witteloostuijn, A. (1999a). Locus of control and strategic behaviour in a prisoner's dilemma game. Personality and Individual Differences, 27, 695-706;Boone, C., De Brabander, B., & van Witteloostuijn, A. (1999b). The impact of personality on behaviour in five Prisoner's Dilemma games, Journal of Economic Psychology, 20, showed that subjects with an internal locus of control were, on average, more cooperative in a prisoner's dilemma (PD) game than subjects with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 18 publications
1
30
0
1
Order By: Relevance
“…10 To the extent that success in markets and other settings depends on the capacity to learn to use a combination of analytic reasoning skills and the ability to understand well others' patterns of thinking and behavior, our findings may shed light on the underlying processes that explain why cognition and character matter and how they interact. Settings in which successful decision-makers need to learn to combine analytic skills and a good theory of mind include sequences of market entry, exit not focus on how character skills influence learning to play equilibrium, although Boone et al (2002) find that sufficient repetition allows subjects with an external locus of control to become more cooperative in the prisoner's dilemma.…”
Section: Opening the Black Box: How Cognition And Character Influencementioning
confidence: 99%
“…10 To the extent that success in markets and other settings depends on the capacity to learn to use a combination of analytic reasoning skills and the ability to understand well others' patterns of thinking and behavior, our findings may shed light on the underlying processes that explain why cognition and character matter and how they interact. Settings in which successful decision-makers need to learn to combine analytic skills and a good theory of mind include sequences of market entry, exit not focus on how character skills influence learning to play equilibrium, although Boone et al (2002) find that sufficient repetition allows subjects with an external locus of control to become more cooperative in the prisoner's dilemma.…”
Section: Opening the Black Box: How Cognition And Character Influencementioning
confidence: 99%
“…CEOs with a high internal locus of control, for instance, are more inclined to pursue innovative and risky strategies than their counterparts with an external locus of control (Miller, Kets de Vries, & Toulouse, 1982), even when they operate in the same market environment (Boone et al, 1996). In a Prisoner's Dilemma context, externals are less inclined to play cooperatively than internals (Boone, De Brabander, & van Witteloostuijn, 1999), and they learn payoff-maximizing behavior more slowly (Boone, De Brabander, Carree, de Jong, van Olffen, & van Witteloostuijn, 2002). These fundamental differences between internals and externals are likely to cause communication barriers and hamper team integration when internals and externals have to work together.…”
Section: The Impact Of Team Leadershipmentioning
confidence: 99%
“…experiments in the past have studied the impact of both situational (e.g., behavior of the other actors) and dispositional (e.g., personality characteristics or cultural background) determinants of cooperation. For instance, cooperative behavior has been shown to be related to personality characteristics such as locus of control (lester 1992;Boone et al 1999b), demographic characteristics such as gender (cook and sloane 1985;Frank et al 1993;Mason et al 1991), and cooperative versus competitive behavior of the other actor in previous rounds of the game (cox et al 1991). several studies have also investigated the impact of ethnical cultural background on cooperative behavior (cook and chi 1984; cox et al 1991), and found that anglo-americans are more competitively oriented than african and asian americans.…”
Section: Introductionmentioning
confidence: 99%